2020
DOI: 10.1016/j.vetmic.2020.108849
|View full text |Cite
|
Sign up to set email alerts
|

Aloe extract inhibits porcine epidemic diarrhea virus in vitro and in vivo

Abstract: Highlights Aloe extract inhibits PEDV replication in Vero and IPEC-J2 cells in vitro. Aloe extract can inactivate PEDV virions directly. Oral administration of Aloe extract can protect newborn piglets against PEDV infection in vivo .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Aloe vera has a significant inhibitory effect on Herpes simplex virus type 1 , Influenza virus , and Pigeon paramyxovirus type 1 [ 20 , 21 , 22 ]. In addition, our previous study found that Ae can inhibit Porcine epidemic diarrhea virus (PEDV) in vitro and in vivo [ 39 ], which prompted us to determine whether Ae can resist PRRSV infection, another common virus in the pig farms. In our experiment, we found that Ae could inhibit PRRSV infection in Marc-145 and iPAM cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aloe vera has a significant inhibitory effect on Herpes simplex virus type 1 , Influenza virus , and Pigeon paramyxovirus type 1 [ 20 , 21 , 22 ]. In addition, our previous study found that Ae can inhibit Porcine epidemic diarrhea virus (PEDV) in vitro and in vivo [ 39 ], which prompted us to determine whether Ae can resist PRRSV infection, another common virus in the pig farms. In our experiment, we found that Ae could inhibit PRRSV infection in Marc-145 and iPAM cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…IFA was performed to observe PRRSV-infected cells as described previously with some modifications [ 39 ]. Briefly, cells were fixed with 4% paraformaldehyde for 15 min at 4 °C and then permeabilized with 0.2% Triton X-100 for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cells were cultured in Dulbecco’ s modified eagle medium (DMEM) (Hyclone, USA) supplemented with 100 U/mL penicillin, 100 U/mL streptomycin, and 10% fetal bovine serum (FBS) (BOVOGEN, Australia). The maintenance medium for PEDV, SADS-CoV, or PDCoV propagation was DMEM supplemented with 7.5 μg/mL trypsin (Gibco, USA)( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…For swine enteropathogenic CoVs infection prevention, the administration of vaccines and antiviral drugs are important tool. Currently a number of vaccines and antiviral drugs, such as killed, liveattenuated vaccine, shRNA expression vector are widely used to prevent swine enteropathogenic CoVs infection (46)(47)(48)(49). However, it still can not stop the swine enteropathogenic CoVs outbreak, due to they are not optimal in terms of safety and efficacy, and large-scale infections still occur, resulting in the death of large numbers of piglets, causing huge economic losses to the pig industry (23,(50)(51)(52), indicating that a deeper understanding of the pathogenesis of swine enteropathogenic CoVs is needed to develop more effective prevention and control measures.…”
Section: Introductionmentioning
confidence: 99%